Analysis of students' mathematical reasoning ability in class IX in solving SPLDV problems - Wilya Rahma Tresna; Kiki Nia Sania Effendi (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the mathematical reasoning ability of students in one of the State Junior High Schools in Karawang Regency in solving two-variable system of linear equations. The method used is a descriptive method with a qualitative approach. The subjects in this study were 32 students of class IX E. The data collection technique was carried out by giving a mathematical reasoning ability test sheet in the form of a description of 4 questions. The data analysis technique used in this study is based on Miles and Huberman's data analysis technique which consists of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the test scores of students' mathematical reasoning abilities are classified as very low, because there are only 2 students who achieve the KKM score. Then also indicated by the percentage value there are 2 students with a percentage of 6% in the high category, 23 students with a percentage of 72% in the medium category and 7 students with a percentage of 22% in the low category.